Gonadotropins in assisted reproductive technology programs: A review - Sabina Ya. Ostrina; Olga F. Serova; Elena B. Rudakova; Elena A. Fedorova (IP Berlin A.V., 2024)
Reproductive medicine is actively developing, and new methods, drugs, and protocols are being developed and introduced for the treatment of infertility. Assisted reproductive technologies (ART) are the most effective methods. In ART protocols, ovarian stimulation (OS) is based on gonadotropin use. The choice of the starting dose of gonadotropin is a critical factor in the successful OS and the effectiveness of ART programs. The article describes the development history of gonadotropins and provides current data on their use in ART programs. The use of biosimilars of follitropin alfa in OS is discussed, and the effectiveness of its Russian biosimilar is also addressed. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back